Robotic Service Quality Success in Increasing Purchase Intention and Customer Satisfaction: A Study of Five-Star Hotels in Egypt - Nafei, Wageeh A.; Khanfar, Nile M.; Mujtaba, Bahaudin G. (Archives of Business Research, 2025)
The objective of this research is to examine the role of potential robotic service quality (RSQ) in increasing purchase intention and customer satisfaction. To assess RSQ and customer satisfaction, we adopted a sampling method to collect data from customers at five-star hotels in Egypt. A total of 300 responses confirmed that automation, personalization, efficiency, and precision significantly and positively influenced purchase intention and customer satisfaction. It is imperative to understand how RSQ may affect customer attitudes and behaviors. RSQ can also be integrated into e-service to present a broader perspective on the quality of web-based services. RSQ can be applied to relevant industries and organizations that extensively use service robots to provide customer service. RSQ can help providers address the advantages and disadvantages of robotic services. RSQ can be a useful tool for them to communicate with service providers to address their appreciation and concerns. The study suggests that five-star hotels in Egypt can improve purchase intention. The study observes that there is a critical shortage of RSQ in Egypt and that a greater understanding of the factors that influence purchase intention is needed.